Alcohol and injury risk at a Western Australian school Leavers Festival - Enkel, S.; Nimmo, L.; Jancey, Jonine; Leavy, J. (Australian Health Promotion Association, 2018)
Background: Leavers Festivals have become an institution for Australian youth to celebrate the completion of secondary school. Reported hazardous consumption of alcohol by leavers has focused concern on risk-taking behaviour. In response to this, campaigns such as "Don't Drink and Drown" have targeted youth to reduce alcohol consumption during aquatic activities. This research investigated intended and actual alcohol consumption, particularly during aquatic activities at a Leavers Festival located in the coastal town of Dunsborough, southern Western Australia. Method: In November 2016, 549 leavers aged 17 or 18 years completed a paper-based survey over a four-day period during the Festival. Results: Overall, 90% of leavers reported intending to drink during the Festival, with expected average daily consumption being 7-9 standard drinks; reported daily consumption was 5-6 standard drinks (P < .001). Of the 29% of leavers who consumed alcohol around water during Leavers, 47% had done so while swimming. About 91% were aware of the campaign "Don't Drink and Drown." Conclusion: Awareness of the "Don't Drink and Drown" campaign and knowledge of risks associated with alcohol consumption and swimming were relatively high. Intention and actual consumption of alcohol did not correlate, with daily consumption less than anticipated. So what: Leavers appear to have a reasonable level of awareness and knowledge of the risks associated with alcohol consumption and aquatic activities, which may reflect the impact of education campaigns. However, this knowledge is not always translated into non-risky aquatic behaviour.